2018
DOI: 10.1088/1361-6455/aac6f2
|View full text |Cite
|
Sign up to set email alerts
|

Energy-level crossings and number-parity effects in a bosonic tunneling model

Abstract: An exactly solved bosonic tunneling model is studied along a line of the coupling parameter space, which includes a quantum phase boundary line. The entire energy spectrum is computed analytically, and found to exhibit multiple energy-level crossings in a region of the coupling parameter space. Several key properties of the model are discussed, which exhibit a clear dependence on whether the particle number is even or odd. Principal among these is a numberparity effect in the quantum dynamics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…This results from the block diagonalization of the Hamiltonian into the different angular momentum representations H N l at = U 1 /2. A similar behaviour is observed in the two-mode Bose Hubbard model with atom-pair tunneling along the boundary between phase-locking and self-trapping phases [56,57]. Indeed, rotating the basis (40) by π/2 and setting U 2 = 0, we have…”
Section: Properties Of the Tight-binding Hamiltoniansupporting
confidence: 76%
“…This results from the block diagonalization of the Hamiltonian into the different angular momentum representations H N l at = U 1 /2. A similar behaviour is observed in the two-mode Bose Hubbard model with atom-pair tunneling along the boundary between phase-locking and self-trapping phases [56,57]. Indeed, rotating the basis (40) by π/2 and setting U 2 = 0, we have…”
Section: Properties Of the Tight-binding Hamiltoniansupporting
confidence: 76%
“…More recently, mean field phase diagrams for double well scenarios in configuration space with pair-tunneling have been discussed in Refs. [25,26].…”
Section: Ground State Phase Diagram a Zero Temperaturementioning
confidence: 99%
“…For example, the two modes could be p x -and p y -orbitals in the first excited state of a two-dimensional (2D) harmonic oscillator. The flavour-changing character of the interaction mimics a pair tunneling term between the two single-particle modes [19][20][21][22][23][24][25][26] and as such it should act to induce coherence between these modes, in contrast to flavour conserving interactions, which tend to inhibit coherence [11]. It is found that the quantum ground state is well approximated as a coherent (for zero temperature) or incoherent (at low temperature) superposition of two quasi-classical phase states, each of which can be realized in a mean-field description via spontaneous symmetry breaking.…”
Section: Introductionmentioning
confidence: 99%